Tonal polarity in Sylheti in the context of noun faithfulness. (September 2018) - Mahanta, Shakuntala; Gope, Amalesh
Abstract: The extant literature (Smith, 2000a, b, 2001, 2002) on differences between nouns versus verbs in phonology has shown that nouns enjoy a privileged status in exhibiting phonological contrasts and processes at the expense of verbal domains. In this paper, we show from original work on Sylheti tones that verbs exhibit exceptionally marked tonal polarity and dominant suffixes which are not seen in nouns. This does not lead to more contrasting patterns in nouns but nouns are faithful. Noun faithfulness can be taken care of by a general faithfulness constraints. Verbs however, need a conjoined markedness and faithfulness constriant ranked higher than the general Faithfulness and Markedness constraints, showing the presence of a putative marked structure in verbs than in nouns. Highlights: Tonal polarity has been found to exist in Sylheti, a highly underdescribed language. Nominal suffixes are assigned a tone which is opposite to that of the root. Tonal polarity in verbs affect verb roots. They are lowered by high toned suffixes. Tonal polarity in verbs is more marked. Nouns are faithful but they do not require a special faithfulness constraint to protect them.